Navigating pulmonary hypertension: Echocardiography insight into right ventricular function and dynamics - Rahmawati, Novi; Yogibuana, Valerinna (Heart Science Journal, 2025)
Pulmonary hypertension (PH) is a pathophysiological disorder characterized by pulmonary vascular remodeling and dysfunction, which may arise in various clinical contexts, particularly in association with cardiovascular and respiratory diseases. PH is characterized by a mean pulmonary arterial pressure (mPAP) exceeding 20 mmHg at rest as determined by hemodynamic assessment via right heart catheterization (RHC), which remains the gold standard for diagnosis. Transthoracic echocardiography (TTE) is recommended as a non-invasive screening tool for the initial evaluation of individuals presenting with symptoms, risk factors, or clinical suspicion of PH. Echocardiography enables the identification of pulmonary hypertension by assessing right ventricular (RV) dysfunction and increased RV pressure overload. A comprehensive assessment of the RV’s dimensions and function is essential in all individuals with PH, given that mortality in PH is correlated with the severity of RV dysfunction. While RHC remains the definitive diagnostic modality for PH, echocardiography provides a valuable, widely available, and non-invasive alternative for estimating pulmonary artery pressures, assessing RV function, and stratifying disease severity, in alignment with current guidelines from the European Society of Cardiology (ESC) and the European Respiratory Society (ERS).